Deformation behavior and stress states of a diffusional creeping polycrystal with bimodal grain-size distribution (Archives of Mechanics - Test, 2010)
Diffusional creep of a polycrystal with bimodal grain-size distribution is examined with spherical-grain approximation. Deformation behavior and stress states of the polycrystal are formulated when grain-boundary sliding occurs much more rapidly than diffusion. Two distinct effects of the grain-size distribution are discussed; the appearance of an initial transient stage in a creep curve of the polycrystal, and the stress concentration of deviatoric components generated at the center of larger grains.